Implementation Of Article 86 Of Law Number 13 Of 2003 Concerning Manpower,Occupational Safety And Health Toward Operator Of Gas Station number 21.381.09 At rawa Makmur Of Bengkulu City - Sukma Jumiati; Ganefi Ganefi; Candra Irawan (Bengkoelen Justice : Jurnal Ilmu Hukum, 2022)
Regarding labour protection, therefore the Law Number 13 of 2003 concerning Manpower,Article 86 Paragraph (1) Letter a and Paragraph (2) states that:"Every worker/labourer has the right to receive protection on occupational safety and health". Then, the researchers will discuss the implementation of article 86 of law number 13 of 2003 concerning Manpower, occupational safety and health toward an operator of the gas station number 21.381.09 at RawaMakmurof Bengkulu City. The aim of this research was to know the implementation ofarticle 86 of Law Number 13 of 2003 concerning Manpower toward the operator of gas station number 21.381.09 atRawaMakmurof Bengkulu City. This research was an empirical study of qualitative research. The data sources used were secondary and primary data sources. In collecting the data, the researcher used interview, observation and documentation. After doing research, it can be concluded the following: Legal Protection at the gas stationare done by using Security Administration Body for Employment (BPJS Ketenagakerjaan) and Healthcare Security (BPJS Kesehatan), and conducted directly protection by the company by providing sweetened condensed milk as a neutralizing immune system, protective footwear shoes, and fire extinguishers as firefighters.